(untitled) (American Journal of Islam and Society, 2006)
This workshop, co-organized by the Regional Studies Program, Walailak University, Thailand, and the Department of Cross-cultural and Regional Studies, University of Copenhagen, Denmark, and conceived of early in 2005, took place a little over a week before the eruption of the “cartoon controversy,” which brought the issue of the relationship between Europe and the so-called “Muslim world” to the fore as never before. From January 20-22, 2006, a group of almost thirty Muslim and non-Muslim specialists working in Islamic studies and on the study of Muslim societies from fifteen countries in Europe and Southeast Asia gathered in Nakhon Sri Thammarat, Thailand, to discuss the diverse “Voices of Islam” in these two regions. The workshop was held in southern Thailand, where, in the ethnic Malay-majority border provinces, a violent insurgency over the last two years has claimed over 1,000 lives and has heightened tensions between the local Muslim population and the Thai state. Some observers have explained the intensification of the conflict as being due to the infiltration of foreign Islamist militants and the influence of extremist Islamic discourses of struggle. The workshop focused on two major themes: how events following the September 11 attacks have affected the nature of Islamic studies in Europe and Southeast Asia, and how changes in Islamic studies are impacting upon Muslims and their understanding of Islam in these two regions. While the workshop presentations were given mainly in English (with a small number of papers presented in Thai and Malay), a simultaneous interpreting service was available for local Thai Muslim (as well as non-Muslim) participants, who attended the workshop in significant numbers. A wide variety of papers were presented. However, if one theme could summarize the tone of the three days, it is that 9/11 has engendered a changing paradigm in these regions’ Islamic studies programs, even though many of the changes may already have been underway prior to the attacks. In the case of Southeast Asia, governments and the media in the region have attributed the Muslim extremists’ ideology, at least partly, to the influence of ...